Pengaruh Budaya Organisasi, Dukungan Organisasi Dan Keterlibatan Kerja Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Pada PDAM Pasaman Barat - Yerismal; Jamil, Muhammad (Journal of Science Education and Management Business, 2022)
Abstract. This study aims to examine how big the influence of organizational culture, organizational support and work involvement on employee performance with organizational commitment as an intervening variable at West Pasaman PDAM. The method of collecting data is through surveys and distributing questionnaires, with a sample of 64 respondents. The analytical method used is multiple linear regression analysis and path analysis using SPSS. The results obtained based on the Partial Test (t test) obtained Organizational Culture and Organizational Support have a significant effect on Organizational Commitment. Work Involvement has no significant effect on Organizational Commitment. Then Organizational Culture, Work Involvement and Organizational Commitment have a significant effect on Employee Performance. There is no significant effect between Organizational Support on Employee Performance. Organizational Commitment does not mediate the influence of Organizational Culture on Employee Performance. Organizational Commitment does not mediate the effect of Organizational Support on Employee Performance. Organizational Commitment does not mediate the effect of Job Involvement on Employee Performance. The contribution of the independent variables of Organizational Culture, Organizational Support and Work Involvement to the dependent variable of Organizational Commitment is 75.9%. While the remaining 23.1% is influenced by other variables outside of this study. The independent variable contribution contribution of Organizational Culture, Organizational Support, Work Involvement and Organizational Commitment to the dependent variable of Employee Performance is 91.4%. While the remaining 8.6% is influenced by other variables outside of this study